PENGARUH LINGKUNGAN KERJA, BUDAYA ORGANISASI DAN GAYA KEPEMIMPINAN TERHADAP DISIPLIN KERJA KARYAWAN PT SWAPRO INTERNATIONAL JAKARTA - Sayidina Iqbal, (2022)
This study aims to determine and prove the influence of the work environment, organizational culture and leadership style on the work discipline employees of PT Swapro International Jakarta. This research is a quantitative research. The sample used in the study amounted to 48 people. The sampling technique used in this study is a saturated sample. The analysis carried out in this study using the SmartPLS 3.2.9 application. The results of the study obtained (1) there is a positive and significant influence between the work environment on employee work discipline (2) there Is a positive and significant influence between organizational culture on employee work discipline (3) there is a positive and significant effect between leadership style on employee work discipline (4) and simultaneously there is a positive and significant influence between work environment, organizational culture and leadership style on employee work discipline.